PENGARUH LOCUS OF CONTROL, EFIKASI DIRI DAN KECERDASAN SPIRITUAL TERHADAP KEPUASAN KERJA DAN IMPLIKASINYA PADA KINERJA GURU SEKOLAH ISLAM TERPADU KABUPATEN BIREUEN - Bakhtiar Bakhtiar; M. Yusuf (LPPM-UNIKI, 2023)
This research was conducted on teachers at the Integrated Islamic School in Bireuen District using a quantitative method with an associative type and using path analysis. Based on the results of the study (1) with a structural model between locus of control, self-efficiency and spiritual intelligence on job satisfaction. Partially, locus of control has a significant effect on teacher job satisfaction, as well as the aspect of self-efficacy has an effect on teacher job satisfaction, and spiritual intelligence has a significant effect on teacher job satisfaction. (2) From the structural model between Locus of control, self-efficacy and spiritual intelligence on teacher performance. So partially Locus of control has a significant effect on teacher performance. In addition, self-efficacy has a significant effect on teacher performance, and spiritual intelligence has a significant effect on teacher performance. (3) Job satisfaction has a significant and positive effect on teacher performance. Job satisfaction can mediate the effect of locus of control on teacher performance. Likewise, job satisfaction can mediate the effect of self-efficacy on teacher performance and job satisfaction can mediate the effect of spiritual intelligence on teacher performance. (4) Locus of control, self-efficacy and spiritual intelligence jointly affect teacher job satisfaction and locus of control, self-efficacy and spiritual intelligence jointly influence teacher performance in Integrated Islamic Schools in Bireuen District.